Transformasi Inovasi Pelayanan Publik menuju Pemerintahan Digital - Sangaji, Muhammad Salman Jabbar; Irianto, Jusuf (Jejaring Administrasi Publik, 2025)
The digitalization of public services is an integrative process involving the application of information and communication technologies (ICT) in the administration of government services to the public. Its primary goal is to enhance efficiency, effectiveness, and the overall quality of public service delivery. By utilizing digital platforms, citizens can swiftly access information and perform various transactions without the need for physical visits to government offices. This study aims to analyze the transformation of public service innovation toward the development of digital government, using a descriptive qualitative approach. Data were collected through document analysis, in-depth interviews, and observation of digital service practices implemented by selected public agencies. Purposive sampling was applied to identify key informants. The findings reveal that the success of public service digitalization depends significantly on effective coordination among stakeholders, infrastructure readiness, human resource capabilities, and institutional willingness to reform existing procedures. Collaboration between the public and private sectors plays a crucial role in the design, implementation, and management of responsive and inclusive digital service systems. Furthermore, the study emphasizes that a strong understanding of public administration principles (transparency, participation, and accountability) must be aligned with technological adaptability to create modern, integrated, and citizen-oriented public services. Keywords: Digitalization, public Services, transformation